Initial Management of Noncastrate Advanced, Recurrent, or Metastatic Prostate Cancer: ASCO Guideline Update. Issue 11 (10th April 2021) - Virgo, Katherine S.; Rumble, R. Bryan; de Wit, Ronald; Mendelson, David S.; Smith, Thomas J.; Taplin, Mary-Ellen; Wade, James L.; Bennett, Charles L.; Scher, Howard I.; Nguyen, Paul L.; Gleave, Martin; Morgan, Scott C.; et al.
Abstract : PURPOSE: Update all preceding ASCO guidelines on initial hormonal management of noncastrate advanced, recurrent, or metastatic prostate cancer. METHODS: The Expert Panel based recommendations on a systematic literature review. Recommendations were approved by the Expert Panel and the ASCO Clinical Practice Guidelines Committee. RESULTS: Four clinical practice guidelines, one clinical practice guidelines endorsement, 19 systematic reviews with or without meta-analyses, 47 phase III randomized controlled trials, nine cohort studies, and two review papers informed the guideline update. RECOMMENDATIONS: Docetaxel, abiraterone, enzalutamide, or apalutamide, each when administered with androgen deprivation therapy (ADT), represent four separate standards of care for noncastrate metastatic prostate cancer. Currently, the use of any of these agents in any particular combination or series cannot be recommended. ADT plus docetaxel, abiraterone, enzalutamide, or apalutamide should be offered to men with metastatic noncastrate prostate cancer, including those who received prior therapies, but have not yet progressed. The combination of ADT plus abiraterone and prednisolone should be considered for men with noncastrate locally advanced nonmetastatic prostate cancer who have undergone radiotherapy, rather than castration monotherapy. Immediate ADT may be offered to men who initially present with noncastrate locally advanced nonmetastatic disease who have not undergone previous local treatment and are unwilling or unable to undergo radiotherapy. Intermittent ADT may be offered to men with high-risk biochemically recurrent nonmetastatic prostate cancer. Active surveillance may be offered to men with low-risk biochemically recurrent nonmetastatic prostate cancer. The panel does not support use of either micronized abiraterone acetate or the 250 mg dose of abiraterone with a low-fat breakfast in the noncastrate setting at this time. Additional information is available at www.asco.org/genitourinary-cancer-guidelines .